Dissatisfaction with Nasal Tip Shape: Secondary Tip Maneuvers - Moyer, Jeffrey S. (Facial Plastic Surgery, 2018)
Dissatisfaction with the appearance of the nasal tip is a common compliant in patients seeking revision surgery after rhinoplasty. Revision rhinoplasty is more technically difficult and unpredictable given the frequent presence of scar contracture, impaired skin envelope quality, and missing alar cartilage. This article describes some of the more common causes for tip revision surgery and techniques to address these abnormalities.
Keywords: rhinoplasty; nasal tip; revision surgery; complication